2016
DOI: 10.1091/mbc.e16-06-0430
|View full text |Cite
|
Sign up to set email alerts
|

Stronger net posterior cortical forces and asymmetric microtubule arrays produce simultaneous centration and rotation of the pronuclear complex in the earlyCaenorhabditis elegansembryo

Abstract: Experimental and theoretical approaches are used to demonstrate the importance of asymmetries in microtubule arrays and cortical pulling forces mediated by dynein in positioning the pronuclear complex before nuclear envelope breakdown in the early Caenorhabditis elegans embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…By precise level, we mean that minimal numbers of microtubules and active force generators are required to ensure posterior displacement, but beyond that constraint, the values do not need to be finely tuned, and modest variations can be buffered. Understanding robustness by accounting for a spatial distribution and regulation of force generation is in its principle similar to the contribution of both the asymmetric microtubule array and a LET-99 band to force regulation during centration and orientation of the pronuclei-centrosome complex (59). Indeed, we propose here that the mechanism linking the LET-99 domain and final spindle position relies on spatial restriction of active force generators to a posteriormost crescent.…”
Section: Discussionmentioning
confidence: 69%
“…By precise level, we mean that minimal numbers of microtubules and active force generators are required to ensure posterior displacement, but beyond that constraint, the values do not need to be finely tuned, and modest variations can be buffered. Understanding robustness by accounting for a spatial distribution and regulation of force generation is in its principle similar to the contribution of both the asymmetric microtubule array and a LET-99 band to force regulation during centration and orientation of the pronuclei-centrosome complex (59). Indeed, we propose here that the mechanism linking the LET-99 domain and final spindle position relies on spatial restriction of active force generators to a posteriormost crescent.…”
Section: Discussionmentioning
confidence: 69%
“…We found that p150 CAP-Gly mutants have defects in the centration and rotation of the NCC, which consists of the two centrosomes and the associated female and male pronucleus. Experimental work and biophysical modelling support the idea that centration forces in the one-cell embryo are generated by dyneinmediated cytoplasmic pulling (Kimura & Onami, 2005;Kimura & Kimura, 2011;Shinar et al, 2011), although a centration/rotation model based on cortical pulling forces has also been proposed (Coffman et al, 2016). In the cytoplasmic pulling model, dynein works against viscous drag as it transports small organelles (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…We found that p150 dnc-1 CAP-Gly mutants have defects in the centration and rotation of the NCC, which consists of the two centrosomes and the associated female and male pronucleus. Experimental work and biophysical modelling support the idea that centration forces in the one-cell embryo are generated by dynein-mediated cytoplasmic pulling [ 5 , 63 , 64 ], although a centration/rotation model based on cortical pulling has also been proposed [ 68 ]. In the cytoplasmic pulling model, dynein works against viscous drag as it transports small organelles (e.g.…”
Section: Discussionmentioning
confidence: 99%